Recent Developments About the Pathogenesis of Dry Eye Disease: Based on Immune Inflammatory Mechanisms - Yu, Lifei; Yu, Chunjing; Dong, He; Mu, Yanan; Zhang, Rui; Zhang, Qiaosi; Liang, Wei; Li, Wenjia; Wang, Xun; Zhang, Lijun (Frontiers in Pharmacology, 2021)
Dry eye disease is a common and frequently occurring ophthalmology with complex and diverse causes, and its incidence is on the upward trend. The pathogenesis of DED is still completely clear. However, the immune response based on inflammation has been recognized as the core basis of the disease. In this review, we will systematically review the previous research on the treatment of DED in immune inflammation, analyze the latest views and research hotspots, and provide reference for the prevention and treatment of DED.